Magnetic Properties of Ancient Sediments Bengawan Solo, Central Java-East Java, Indonesia - Legowo, Budi; Putra, Shandiyano; Purwanto, Heri; Rifai, Hamdi; Suryanto, Wiwit; Purnama, Budi (Trends in Sciences, 2022)
Information about the eruption of Mount Lawu in Central Java Province in 1885 and Mount Merapi in D.I. Yogyakarta in 2010 became a source for estimating the presence of magnetic minerals which underwent a sedimentation process in the Bengawan Solo River from upstream (Wonogiri) - downstream (Bojonegoro). The results we get of the magnetic susceptibility distribution of the Bengawan Solo sediments reveal that the sediment from the upper reaches of the Bengawan Solo River has a low frequency magnetic susceptibility value in upstream of around 1,080.23×10−8 m3/Kg - 2,780.77×10−8 m3/Kg, the middle part is 74.40×10−8 m3/Kg - 1,735.90×10−8 m3/Kg, and downstream 17.57×10−8 m3/Kg - 1,620.53×10−8 m3/Kg. The value of magnetic susceptibility decreased significantly from upstream to downstream. High susceptibility indicates the sample contains metal elements. In determining iron oxide, we use X-Ray Fluorescence assisted by X-Ray Diffractometer testing to determine magnetic minerals. X-Ray Fluorescence confirm metal oxide in the sample. There are Al and Fe confirm the presence of magnetic properties in sedimentation. The Vibrating Sample Magnetometer confirmed that the Bengawan Solo sediment has a magnetic saturation about 0.06 - 9.50 (emu/g), a magnetic remanent around 0.001 - 0.575 (emu/g) and coercivity field of around 10 - 60.15 (Oe). X-Ray Diffractometer pattern confirm the mineral structures, namely Coesite, Magnetite, Cristobalite, Portlandite, Quartz, Anatase, Goethite, Tridymite, Gibsyte, Stishovite, Grasullaria, Labradorite and Wuestite. These results indicate the novelty of sediments from Bengawan Solo, Central Java to East Java. HIGHLIGHTS We found several important points in this research: The Bengawan Solo River is formed from several formations and lifting from faults The Bengawan Solo River is rich in minerals formed from metal oxides The magnetic value decreases with the distance from Mount Lawu The Bengawan Solo River has confirmed ferromagnetic properties from the S-type hysterisis curve With low magnetic remanent values, low saturation magnetism and high magnetic corrosivity GRAPHICAL ABSTRACT